Rancang Bangun Sistem Informasi Manajemen Aset Teknologi Informasi Pada PT. PELINDO III Cabang Perak Surabaya - Syaiful Riza Hidayatullah; Sulis Janu Hartati; Pantjawati Sudarmaningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Division SMI (System Management information) is one of the divisions of PT. Pelindo  III Perak Surabaya. SMI division responsible for the management of IT assets (information technology) that exist on the PT. PELINDO III. The information such as the information value of IT assets, IT asset maintenance history information, information utilization of IT assets, and any PC information that can be implemented new software. In the absence of such information resulted in the division of SMI often have problems such as: do not know how much IT assets owned today, do not know which software assets are going to expire, maintenance of IT assets that are not scheduled, determine asset PC anywhere that can be installed new software, and any PC assets to do updates. In this study, these problems can be solved by building a system able to manage IT assets at PT. Pelindo III. The system in question is the IT asset management information system that can manage the system from the beginning of the life cycle of IT assets (procurement), the use of IT assets (utilization), and until the end of the life cycle of an asset (disposal assets).